SPIRITUAL LEADERSHIP AND EMPLOYEE HELPING BEHAVIOUR: THE ROLES OF THRIVING AT WORK AND ETHICAL CLIMATE - Abraham Ansong; Moses Ahomka Yeboah; Alberta Talata Ankomah (PEOPLE: International Journal of Social Sciences, 2025)
The study examined the influence of leaders’ spiritual values on the willingness of employees to help each other to perform better on the job and the extent to which individual and organisational factors, such as thriving at work and ethical climate mediates and moderates the relationship, respectively. We employed quantitative approach to collect data from health workers and used the partial least squares structural equation modelling (PLS -SEM) technique to test the hypotheses in the study. The study established that leaders’ use of spiritual values influence the helping behaviour of health workers. Also, health workers’ thriving at work mediates the relationship between spiritual leadership and their helping behaviours. However, the ethical climate in the workplace does not moderate the relationships between spiritual leadership and health workers’ helping behaviours. Organizations should provide trainings programs to nurture and build leaders’ spiritual values as well their ability to develop and meet health workers’ spiritual values. It is also imperative for organizations to improve health workers’ helping behavior through programs or activities on building their motivation and confidence to thrive at work. We offer a more nuanced understanding of employees’ helping behaviour by incorporating critical individual and organisational boundary conditions through which leaders could use spiritual values to further drive employees (health workers) to support each other in attaining organisational goals (quality health care).